Konsep Karya Hiliran (Budaya Dan Masa Kini) - Ni Komang Sri Wahyuni (Mudra Jurnal Seni Budaya, 2008)
Through various exploration and the research show in rural, in coast, non in stsge by using special settlement, as everyday refleksi life of society of Tejakula Village, what more signalizing of natural element and natural. This matter is with the Fistula meaning underside, representing Pate; Upstream antonym (upper). Settlement naturally in areal staging in the form of black sand with its cobblestones, grove become green in coastal periphery, free sea and small river stream, made by as very supporting shares of masterpiece perfection. left and Right backside of staging place attached by penjor and twenty umbul-umbul. Rear instrument of gambelan of Gong Kebyar to accompany the appearance of Krama Negak village, Krama Cendek and training dance the Kebyar Tarunajaya. In sea front, in bamboo tide to drape the net, what is being improve; repaired by all fisherman. In starboard, attached by place of grilling of haul fish of all fisherman.